THE EFFECT OF EMPLOYEE MOTIVATION AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH JOB SATISFACTION AS A MEDIATING VARIABLE (A CASE STUDY AT PT METAL SMELTINDO SELARAS) - Rohmatullah; Asti Nur Aryanti; Gurawan Dayona; Nunung Ayu Sofiati; Ridlwan Muttaqin (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of employee motivation and organizational culture on organizational citizenship behavior (OCB), with job satisfaction as a mediating variable at PT Metal Smeltindo Selaras. The research employs a quantitative approach using a survey method, involving 160 employees as the sample. The sampling technique used is Proportionate Stratified Random Sampling. Data were collected through questionnaires and analyzed using descriptive statistics and path analysis. The results show that employee motivation has a positive and significant effect on job satisfaction and OCB, and organizational culture also has a positive and significant effect on job satisfaction and OCB. Job satisfaction is proven to have a positive and significant effect on OCB. Furthermore, job satisfaction partially mediates the influence of employee motivation and organizational culture on OCB. These findings indicate that increasing employee motivation and fostering a conducive organizational culture will enhance job satisfaction and OCB, which in turn can improve company performance and productivity.